Cerebral palsy and developmental intellectual disability in children younger than 5 years: Findings from the GBD-WHO Rehabilitation Database 2019 - Olusanya, Bolajoko O.; Gladstone, Melissa; Wright, Scott M.; Hadders-Algra, Mijna; Boo, Nem-Yun; Nair, M. K. C.; Almasri, Nihad; Kancherla, Vijaya; Samms-Vaughan, Maureen E.; Kakooza-Mwesige, Angelina; Smythe, Tracey; del Castillo-Hegyi, Christie; et al. (Frontiers in Public Health, 2022)
Objective Children with developmental disabilities are associated with a high risk of poor school enrollment and educational attainment without timely and appropriate support. Epidemiological data on cerebral palsy and associated comorbidities required for policy intervention in global health are lacking. This paper set out to report the best available evidence on the global and regional prevalence of cerebral palsy (CP) and developmental intellectual disability and the associated “years lived with disability” (YLDs) among children under 5 years of age in 2019. Methods We analyzed the collaborative 2019 Rehabilitation Database of the Global Burden of Disease (GBD) Study and World Health Organization for neurological and mental disorders available for 204 countries and territories. Point prevalence and YLDs with 95% uncertainty intervals (UI) are presented. Results Globally, 8.1 million (7.1–9.2) or 1.2% of children under 5 years are estimated to have CP with 16.1 million (11.5–21.0) or 2.4% having intellectual disability. Over 98% resided in low-income and middle-income countries (LMICs). CP and intellectual disability accounted for 6.5% and 4.5% of the aggregate YLDs from all causes of adverse health outcomes respectively. African Region recorded the highest prevalence of CP (1.6%) while South-East Asia Region had the highest prevalence of intellectual disability. The top 10 countries accounted for 57.2% of the global prevalence of CP and 62.0% of the global prevalence of intellectual disability. Conclusion Based on this Database, CP and intellectual disability are highly prevalent and associated with substantial YLDs among children under 5 years worldwide. Universal early detection and support services are warranted, particularly in LMICs to optimize school readiness for these children toward inclusive education as envisioned by the United Nations' Sustainable Development Goals.